A Sendai Framework-Based Assessment of Disaster Risk Management in the Municipalities of Northern Samar: Basis for Enhancing the Local DRRM Plan - Camarillo, Saul (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed disaster risk management knowledge among municipalities in Northern Samar using the four priority areas of the Sendai Framework for Disaster Risk Reduction (2015–2030) and examined its relationship with selected municipal profile characteristics. Guided by the Sendai Framework and supported by Resource Dependence Theory and Human Capital Theory, the study employed a quantitative descriptive-correlational research design. Data were collected through a researcher-developed and validated questionnaire administered to local government officials and personnel directly involved in disaster risk reduction and management activities across the municipalities of Northern Samar. Descriptive and inferential statistics, including frequency counts, percentages, weighted means, and Pearson Product-Moment Correlation Coefficient, were used in analyzing the data. The findings revealed that most municipalities belonged to lower municipal and income classifications, had relatively small populations, were predominantly coastal, and operated within modest fiscal environments. Despite these constraints, respondents demonstrated a very high level of disaster risk management knowledge across most Sendai Framework priority areas. Knowledge was strongest in strengthening disaster risk management governance, followed by disaster preparedness and disaster risk understanding, while investing in disaster risk reduction for resilience received the lowest, though still high, rating. Significant positive relationships were found between disaster risk management knowledge and municipal classification level, income classification, National Tax Allotment allocation, and annual disaster risk reduction and management allocation. In contrast, population size, number of barangays, geographic location, and land area were not significantly related to disaster risk management knowledge. The study concludes that fiscal capacity, institutional commitment, and governance resources play important roles in strengthening disaster risk management competencies among municipalities. Continued investments in capacity development, disaster risk reduction financing, and institutional strengthening are recommended to enhance local resilience and disaster governance. This study supports SDG 11 (Sustainable Cities and Communities) and SDG 13 (Climate Action) by promoting stronger local disaster resilience, preparedness, and risk-informed governance. Its sustainability contribution lies in strengthening institutional capacity, community resilience, and evidence-based disaster risk reduction practices that support long-term sustainable local development.
Keywords: Climate Action; Disaster Governance; Disaster Risk Management Knowledge; Local Government Units; Resilience; Sendai Framework; Sustainable Cities and Communities